Design and characterization of the CLICTD pixelated monolithic sensor chip - Kremastiotis, Iraklis; Ballabriga, R.; Campbell, M.; Dannheim, D.; Dort, K.; Egidos, N.; Kröger, Jens; Linssen, L.; Llopart, X.; Munker, M.; Nürnberg, A.; Peric, I.; et al. (IEEE transactions on nuclear science, 2020)
A novel monolithic pixelated sensor and readout chip, the compact linear collider tracker detector (CLICTD) chip, is presented. The CLICTD chip was designed targeting the requirements of the silicon tracker development for the experiment at the compact linear collider (CLIC) and has been fabricated in a modified 180 nm CMOS imaging process with charge collection on a high-resistivity p-type epitaxial layer. The chip features a matrix of 16 × 128 elongated channels, each measuring 300 × 30 μm2. Each channel contains 8 equidistant collection electrodes and analog readout circuits to ensure prompt signal formation. A simultaneous 8-bit time-of-arrival (with 10 ns time bins) and 5-bit time-over-threshold measurement is performed on the combined digital output of the 8 subpixels in every channel. The chip has been fabricated in two process variants and characterized in laboratory measurements using electrical test pulses and radiation sources. Results show a minimum threshold between 135 and 180 e and a noise of about 14 e- rms. The design aspects and characterization results of the CLICTD chip are presented.
Gesehen am 14.12.2020